Patient acceptability of intravitreal complement inhibitors in geographic atrophy (GA): protocol for a UK-based cross-sectional study - David P Crabb; Deanna J Taylor; Christiana Dinah; Mandeep Sekhon; Jamie Enoch; Arevik Ghulakhszian (BMJ Open)
Introduction Geographic atrophy (GA) is the advanced form of the non-neovascular (‘dry’) type of age-related macular degeneration (AMD). Previously untreatable, complement inhibitors delivered by regular intravitreal injections have recently been demonstrated to slow down the progression of GA lesions in phase 3 trials. One such treatment, Syfovre (pegcetacoplan), was approved by the US Food and Drug Administration in February 2023. These therapies slow down, but do not stop or reverse, the progression of GA; they may also increase the risk of developing the neovascular (‘wet’) type of AMD. In light of these developments, this study aims to quantify the acceptability of these new intravitreal injection treatments to patients with GA in the UK and explore factors that may influence the acceptability of these treatments.Methods and analysis In this cross-sectional, non-interventional study, the primary objective is to determine the proportion of patients with GA that find regular intravitreal therapy acceptable for slowing the progression of GA. We will use a validated acceptability questionnaire in order to quantify the acceptability of new treatments among patients with GA. The correlation between acceptability and functional and structural biomarkers of GA will be established. We will also explore demographic, general health and ocular factors that may influence acceptability. 180 individuals with a diagnosis of GA will be recruited from 7 to 8 participating National Health Service trusts across the UK. Multiple regression analysis will be conducted to determine the simultaneous effects of multiple factors on patient acceptability.Ethics and dissemination The study received ethical approval from the Health Research Authority on 14 March 2023 (IRAS Project ID: 324854). Findings will be disseminated through peer-reviewed publications and conference presentations to the medical retina community, as well as through dialogue with patients and macular disease charities.